“Quem pariu Mateus que o embale”: a transmissibilidade do crédito alimentar para um efetivo acesso à justiça - Nomizo, Sílvia Leiko (2023)
One of the main challenges for legal science is to understand the problem of the lack of effectiveness of the rules, so it turns its attention to the search for instruments to help the law enforcer. The ineffectiveness of the rule is of greater concern when we are faced with the non-realization of human and fundamental rights, given their relevance to all individuals. In this context, the importance of state action, through the Judiciary, in the process of promoting effective judicial provision stands out, ensuring that those who use it have broad access to justice. It is worth remembering that access to justice itself is classified as a human and fundamental right, respectively, in the international and national legal systemsIt so happens that one of the main challenges facing the Judiciary is to make access to justice a reality, especially when faced with a situation in which there is a collision between human and fundamental rights, in which the choice of the appropriate interpretative method is essential if a fair decision is to be made. Among the various methods of interpretation, the adoption of interpretation in accordance with human rights, or in accordance with the Constitution, has gained importance not only in domestic law but also in international law. In view of this growing trend, the practice of family law litigation, especially in the enforcement of alimony claims, it was found that the Superior Court of Justice has ruled, in some specific cases, in a way that is incompatible with interpretation in accordance with human rights. This can be seen from the cases in which the possibility of transferability of maintenance claims is discussed, in the event of the death or lack of interest of the alimony claimant, or if an exoneration action is successful, to those who have been forced to provide for their children on their own, due to the default of the alimony claimant. In the cases in question, the Superior Court of Justice has recently taken the position that transferability is not possible, applying a very restrictive and apparently mistaken interpretation of the legislation. Thus, the aim of this thesis is to analyze the precedents of the STJ on the non-transferability of maintenance claims, based on an interpretation in line with human rights, with the aim of presenting a theoretical and practical solution to such an important issue. To prepare this thesis, the qualitative and deductive method was adopted and the data was obtained through bibliographical and documentary research, in printed and digital materials. It can be concluded that the nontransferability of maintenance claims represents an obstacle to the realization of important human rights, compliance with which is mandatory in legal proceedings, since it encourages non-payment of maintenance and damages the dignity of those who bear all the costs of supporting their children alone